Shake table testing of hybrid wood shear wall system - Anandan, Yeshwant Kumar, author; van de Lindt, John, advisor; Jia, Gaofeng, committee member; Chong, Edwin K. P., committee member (Colorado State University. Libraries, 2019)
Cross-Laminated Timber (CLT) is an engineered, prefabricated mass timber product that has shown excellent structural and mechanical properties. With the growing application of CLT in industry, there have been a number of research projects carried out to introduce CLT in tall buildings located in high seismic regions. The concept of post-tensioning mass timber has been adopted from concrete systems and this led to development of seismically resilient structural systems that can undergo multiple earthquake and continue to re-center. This thesis presents the results of a shake table test program that focused on testing of a one-story full-scale hybrid wood shear wall system comprised of a post-tensioned CLT wall panel with Light-frame wood shear (LiFS) wall panels on each side. The testing was conducted at CSU's Engineering Research Center shake table. The objective of this study was to combine the advantages of the post-tensioned CLT systems with those of LiFS walls. The hybrid shear wall system in the testing had two LiFS walls on either side of a post-tensioned rocking CLT wall panel. Mild steel rods were used as post-tensioning rods in this experiment and the test structure also included gravity frames constructed with wood studs (but no sheathing) and a CLT floor diaphragm to support a seismic weight of 12,000 lbs. The structure was subjected to the 1989 Loma Prieta ground motion record scaled to different intensities. The final test used the original 1994 Northridge ground motion record from the Rinaldi record station, with a slight reduction to be able to be accommodated by the 20 inch shake table actuator stroke. This test was conducted to understand the collapse mechanism of the structure and demonstrated the ability of the post-tensioned CLT to re-center the structure after 5% inter-story drifts and also the ability of the LiFS walls to act as energy dissipation and lateral force resisting systems.
Keywords: hybrid system; post-tensioning; light-frame wood; cross-laminated timber